Maturation and beyond: proteins in the developmental continuum from enamel epithelium to junctional epithelium - Ganss, Bernhard; Abbarin, Nastaran (Frontiers in Physiology, 2014)
Enamel, covering the surface of teeth, is the hardest substance in mammals. It is designed to last a lifetime in spite of severe environmental challenges. Enamel is formed in a biomineralization process that is essentially divided into secretory and maturation stages. While the molecular events of enamel formation during the secretory stage have been elucidated to some extent, the mechanisms of enamel maturation are less defined, and little is known about the molecules present beyond the maturation stage. Several genes, all located within the secreted calcium-binding phosphoprotein (SCPP) gene cluster, were recently shown to be expressed during the developmental continuum from maturation stage ameloblasts to junctional epithelium. This review introduces four such genes and their protein products, and presents our current state of knowledge on their roles, primarily in enamel formation and junctional epithelium biology. The discovery of these proteins, and a more detailed analysis of their biological functions, will likely contribute to a more thorough understanding of the molecular mechanisms of enamel maturation and dentogingival attachment.